IFAS Community Development: Empowering Your Community, Stage 1, Initiation - Jade Marcus; Mark A. Brennan (EDIS)
This paper is part of a series of discussions on community development. This series includes specialized papers on civic engagement, community action, and other topics important to the development of community. This document is FCS 9210, of a series of the Department of Family, Youth and Community Sciences, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2005.